Circular RNA in disease: Basic properties and biomedical relevance. (22nd February 2022) - Chen, Xiaolan; Zhou, Min; Yant, Levi; Huang, Chuan
Abstract: Circular RNAs (circRNAs) represent a class of covalently closed RNA molecules with great diversity in molecular features, functions, and regulatory mechanisms. Emerging advances in our understanding of circRNA biogenesis, nuclear export, and stability control have been made very recently. In particular, novel roles of circRNAs in diverse human diseases are increasingly recognized. Various circRNAs have been found to affect many disease‐relevant pathways through a diverse array of mechanisms, including forming R‐loops, sponging miRNAs or proteins, and translating functional proteins, resulting in different pathological phenotypes. This recent progress calls for a revised view of circRNAs in diseases threatening the lives and health of humans. In this review, we focus on the recently described functional relevance of disease‐associated circRNAs as well as the potential of circRNAs in diverse clinical applications. This article is categorized under: RNA in Disease and Development > RNA in Disease Regulatory RNAs/RNAi/Riboswitches > Regulatory RNAs Abstract : An overview graphic of the functional relevance of multiple disease‐associated circRNAs.